Unraveling the Composition of Rembrandt's Impasto through the Identification of Unusual Plumbonacrite by Multimodal X‐ray Diffraction Analysis - Gonzalez, Victor; Cotte, Marine; Wallez, Gilles; van Loon, Annelies; de Nolf, Wout; Eveno, Myriam; Keune, Katrien; Noble, Petria; Dik, Joris (Angewandte Chemie International Edition, 2019)
Rembrandt (1606–1669) is renowned for his impasto technique, involving his use of lead white paint with outstanding rheological properties. This paint was obtained by combining lead white pigment (a mixture of cerussite PbCO3 and hydrocerussite Pb3(CO3)2(OH)2) with an organic binding medium, but the exact formulation used by Rembrandt remains a mystery. A powerful combination of high‐angle and high‐lateral resolution x‐ray diffraction was used to investigate several microscopic paint samples from four Rembrandt masterpieces. A rare lead compound, plumbonacrite (Pb5(CO3)3O(OH)2), was detected in areas of impasto. This can be considered a fingerprint of Rembrandt's recipe and is evidence of the use of an alkaline binding medium, which sheds a new light on Rembrandt's pictorial technique. Importance of impasto: Using high‐resolution X‐ray diffraction spectroscopy, a rare lead compound, plumbonacrite (Pb5(CO3)3O(OH)2), was detected in areas of impasto from paint samples of four Rembrandt masterpieces. This can be considered a fingerprint of Rembrandt's impasto recipe and is evidence of the use of an alkaline binding medium.